The effect of monensin concentration on dry matter intake, ruminal fermentation, short-chain fatty acid absorption, total tract digestibility, and total gastrointestinal barrier function in beef heifers - Wood, K. M.; Pinto, A. C.J. [UNESP]; Millen, D. D. [UNESP]; Kanafany Guzman, R.; Penner, G. B. (Oxford University Press (OUP), 2016)
In a 4 × 4 Latin square design (24-d periods), 4 ruminally cannulated Hereford × Angus/ Simmental heifers were used to evaluate the effect of increasing levels of monensin concentration on DMI, ruminal fermentation, short-chain fatty acid (SCFA) absorption across the reticulorumen, and total tract barrier function. Heifers were fed a barley-based finishing diet (76% rolled barley grain, 12% barley silage, 8% mineral and vitamin supplement, and 4% canola meal) containing 0, 22, 33 or 48 mg/kg monensin. Urinary recovery of Cr-EDTA was used as an indicator of total tract barrier function (d 18 to 20). Days 20 to 23 were used to evaluate ruminal fermentation and total tract digestibility measurements, and SCFA absorption was measured using the temporarily isolated and washed reticulorumen technique on d 24. Data were analyzed using PROC MIXED of SAS with linear and quadratic contrasts to evaluate the effect of increasing monensin dose. Increasing monensin linearly decreased DMI (10.0, 9.9, 9.3, and 9.1 kg/d for diets containing 0, 22, 33 or 48 mg/kg monensin, respectively; P = 0.01) but did not affect the variation in DMI among days. Urinary Cr-EDTA recovery was not (P ≥ 0. 61) affected by increasing dose of monensin, nor was ruminal pH (mean, minimum, maximum, duration less than 5.5, and area under curve; P ≥ 0.21). The acetate-to-propionate ratio linearly decreased (1.9, 1.8, 1.4, and 1.3 for diets containing 0, 22, 33 or 48 mg/kg monensin, respectively; P = 0.03) with increasing monensin. There was no response (P ≥ 0. 17) for the rate of SCFA absorption with monensin concentration. Total tract ethanol soluble carbohydrate digestibility linearly increased (77.2, 84.7, 88.0, and 94.0% for diets containing 0, 22, 33 or 48 mg/kg monensin, respectively; P = 0.003) whereas starch digestibility quadratically responded (93.8, 93.9, 88.0, and 94.0% for diets containing 0, 22, 33 or 48 mg/kg monensin, respectively; P < 0.001), where 33 mg/kg inclusion of monensin had a minimal value. The results from this study indicate that in addition to the known effects of monensin to reduce DMI and the acetate:propionate ratio, monensin inclusion does not affect ruminal pH, SCFA absorption, or total tract barrier function.
Keywords: Barrier function; Monensin; Short-chain fatty acid absorption; Total tract digestibility